Increasing the road safety of e-bike: design of protective shells based on stability criteria - Zhang, Le-Le (2017)
China currently occupies the world’s leading Electric bicycle (e-bike) market. However, the popularity of e-bikes is accompanied by massive numbers of injuries and deaths due to accidents involving e-bikes. As a result, the safety of e-bikes has recently received much attention from the public and the government and researchers have concentrated on improving the safety features of e-bikes with innovative technologies. It has been shown that well-designed protective shells can protect a driver involved in an e-bike accident. However, there is a lack of criteria on which to base the design of an effective protective shell for e-bikes. Therefore, this research focuses on the development of a design criterion based on the specific case of Roly-Poly stability. This stability criterion can be formulated for one curved surface as r > h, which is in a stable stability configuration - one of a number of static stability configurations. In this study, static stabilities are configured based on knowledge of potential energy (PE). In order to verify the design criteria, three types of protective shells are designed with different stability conditions. The first type follows the design criterion (r > h), while the remaining two do not (r = h and r < h). A finite element model of an e-bike is constructed with key components, such as the main frame, CoM (the position of which is obtained by a plumb line experiment), and the designed protective shells. The meshed models are produced and employed to determine the contact parameters using the frictionless penalty method. The corresponding results of sideways falling simulation successfully demonstrate the validity of the design criterion.